Decolourization of Drimarene Orange KGL by Orange (Citrus reticulata) Peroxidase - Hafiz, Nosheen; Nawaz Bhatti, Haq; Nouren, Shazia; Munir, Majid (Asian Journal of Chemistry, 2014)
Reactive dyes are widely employed in textile industries and their removal from wastewaters is a relevant environmental problem. In addition to chemical and physical methods, several bioremediation approaches, involving intact micro-organisms or isolated enzymes have been proposed to decolourize dye solutions. The aim of this study was to evaluate the enzymatic action of partially purified orange (Citrus reticulata) peroxidase for the degradation of industrially important dye Drimarene orange KGL. Studies were carried out to understand the process parameters such as aqueous phase pH, temperature, time, H2O2 dose, dye and enzyme concentrations during enzyme-mediated dye degradation process. Experimental data revealed that 81.36 % degradation of 60 ppm Drimarene orange KGL solution was obtained within 160 min in the presence of 33 U/mL of orange peroxidase, 2 mM H2O2 at pH 4 and 60 °C temperature.